Inbreeding depression in test‑day milk yield of Gyr dairy cattle - Pereira, Rodrigo Junqueira; Santana Júnior, Mário Luiz; Ayres, Denise Rocha; Bignardi, Annaiza Braga; Vercesi Filho, Aníbal Eugênio (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to estimate the effect of inbreeding on milk yield and its persistency during lactation, in Gyr dairy cattle, as well as to determine the impact of considering or not the effect of inbreeding on the genetic evaluation of this trait. Test‑day records (89,490) for milk yield from 11,675 dairy cows at first lactation were used. The individual inbreeding coefficient, the individual increase of inbreeding, and the number of equivalent complete generations of each individual were computed. Inbreeding depression was estimated by including the effect of individual increase of inbreeding in a random regression model. The solutions for inbreeding depression, according to the class of individual increase of inbreeding and stage of lactation, ranged between ‑1.238 and ‑0.135 kg, which indicates a reduction of milk yield with the increase of inbreeding. At higher levels of inbreeding, the persistence of milk yield was reduced. The inclusion of the inbreeding effect in the genetic evaluation model did not affect the genetic parameter estimates, with practically no change of the predicted breeding values and rank of animals. The inbreeding effect can be included in the statistical model for the genetic evaluation of milk yield.